PENERAPAN PROTOKOL CHSE PADA CENTRAL EVENT ORGANIZER SAAT KENORMALAN BARU - Aldira, Kelvin; Sendra, I Made; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
This study focuses on the application of the CHSE (Cleanliness, Health, Safety, and Environment Sustainability) protocol in organizing events at the Central Event Organizer during the new normal. The Covid-19 pandemic has a direct impact on the event organizing industry, where the level of public trust in the event organizing company has decreased, as well as the assumption that organizing events is the cause of mass crowds. The purpose of this study is to find out how the implementation of the CHSE health protocol (Cleanliness, Health, Safety, and Environment Sustainability) at events organized by the Central Event Organizer at the Pre Event, On Event, and Post Event stages. This study uses a non-probability sampling technique with a special technique, namely purposive sampling. The technique of determining informants directly uses the in-depth interview method. The number of informants in this study were 8 informants, which were divided into primary informants and principal informants. The data analysis technique in this study is a qualitative descriptive data analysis technique, namely fixed analysis, using words that are arranged into the text and then expanded. The results of this study are the implementation of new operational procedures in organizing events by the event organizing company properly. These operational procedures have been fully implemented at the Pre Event, On Event, Post Event stages. It is hoped that in the future there will be cooperation from the government in the form of clear rules regarding organizing events in the new normal.